Establishment and optimization of ISSR and SAMPL molecular markers as a tool for breeding programs of Pinus radiata - Moraga-Suazo, Priscila; Hasbún, Rodrigo; Balocchi, Claudio; Valenzuela, Sofía (Bosque (Valdivia), 2017)
Pinus radiata is a conifer of recognized economic value. Studies at genetic and molecular level to support breeding programs of radiata pine have been conducted with difficulty due to its large and complex genome. The development of molecular markers has allowed performing studies on genetic variation, identification of clones and construction of linkage maps. In order to increase the genetic molecular markers in P. radiata, two inter simple sequence repeat (ISSR) markers and twelve selective amplifications of microsatellite polymorphic loci (SAMPL) primer combinations were tested, using a first-generation full-sib family of 86 individuals. Polymerase chain reaction (PCR) products were visualized by capillary electrophoresis and polymorphism was detected by presence or absence of a particular fragment in one P. radiata parental. A total of 18 polymorphic fragments were found for two ISSR primers tested, with an average segregation distortion of 33 %. SAMPL markers yielded 85 polymorphic fragments with eight primer combinations, with an average of 22.3 % segregation distortion. Both methodologies showed a good reproducibility, with easy implementation and useful for genetic analysis on P. radiata.